Karakteristik Fisik, Kimia dan Sensoris Abon Ikan dari Berbagai Ikan Ekonomis Rendah - Hendra Permana Aditya; Herpandi Herpandi; Susi Lestari (Jurnal FishtecH, 2016)
The purpose of this research was to investigate the characteriztics of phisycal, chemical, and sensory shredded fish from various low economic fish. The research was conducted on November until December 2015. By using experimental laboratory methods and data analysis was performed descriptively. The results showed the average value of The water content of Tinfoil Barb, Minnows Carp, Serandang Fish and Bonylip Barb were 11.89%, 8.37%, 8%, and 6.94%. While the ash content that produced by Tinfoil Barb, Minnows Carp, Serandang Fish and Bonylip Barb were 23.65%, 23.09%, 22.17% and 21.9%. Protein content that produced by Tinfoil Barb, Minnows Carp, Serandang Fish and Bonylip Barb were 21.14%, 20.71%, 19.21% and 16.8%. Fat content that produced by Tinfoil Barb, Minnows Carp, Serandang Fish and Bonylip Barb were 21.23%, 20.1%, 19.81% and 17.77%. Carbohydrate content that produced by Tinfoil Barb, Minnows Carp, Serandang Fish and Bonylip Barb were 31.64%, 29.53%, 29.3% and 26.74%. The average value of lightness was from 51.2%-55.43%, Chroma 22%-24.53%, Hue 52.4%-56.67%.